Inflation and Market Structure - Jonathan Nitzan (The Bichler and Nitzan Archives, 1990)
This is the third in a series of three essays which explore modern theories for inflation. Here we examine theories that reject the universal validity of perfect competition and link inflation with alternative, more realistic structures and institutions. In contrast to macroeconomic theories which emphasize `excess demand' and growth inflation, structural theories relate primarily to stagflation. While most macroeconomists share a common belief in the ideal type of `profit maximization,' structural theorists differ widely in their views on what motivates economic actors. The multiplicity of motivational assumptions lead different theorists toward distinct explanations for inflation. With their greater sensitivity toward real institutions, these theories offers important insights into the process of modern inflation. The structural literature, is, nevertheless limited by some of its methodological foundations.
Keywords: 330; business structure; corporate concentration; full-cost; growth; inflation; markup; monopoly; normal price; oligopoly; price smoothing; profit; pull-push spirals; stagflation; stagnation; target rate of return; wages